Implementation of the PIECES Framework and the Effectiveness of the Online Weighbridge System on Road Traffic Safety through Driver Compliance - Kristianto, Jati; Gunawan, Aang; Setiawan, Edhie Budi (Dinasti Publisher, 2026)
Over Dimension and Over Loading (ODOL) violations remain a major contributor to infrastructure degradation and traffic accidents in Indonesia, particularly in Banten Province. The Online Weighbridge System (Jembatan Timbang Online/JTO) at UPPKB Cikande was designed as a technology-based monitoring instrument to mitigate these violations. This study aims to analyze the implementation of the PIECES Framework (Performance, Information, Economics, Control, Efficiency, Service) and the effectiveness of JTO on road traffic safety, with driver compliance acting as a mediating variable. A quantitative approach was employed through a questionnaire survey of 385 freight drivers selected via purposive sampling at UPPKB Cikande, and the data were analyzed using Structural Equation Modeling–Partial Least Square (SEM-PLS) on SmartPLS. The results demonstrate that JTO effectiveness has a positive and significant impact on driver compliance (0.689) and on traffic safety (0.666); Furthermore, driver compliance significantly influences traffic safety (0.294). The PIECES Framework significantly affects both compliance (0.298) and safety (0.314), with compliance serving as a significant mediator in both pathways. The “Performance” and “efficiency” dimensions obtained the highest scores, indicating that JTO has successfully accelerated the weighing process, whereas “service” and “control” require further enhancement. The study concludes that integrating PIECES Framework with JTO operations strengthens compliance and supports safer freight transportation. It recommends the optimization of system technology, supervisory services, and consistent law enforcement to foster adaptive and data-driven transportation policies.